Chloride ion permeation resistant grouting material and application thereof

By adding phenols, formaldehyde, and amino POSS derivatives to offshore wind grouting materials, the corrosion and deterioration of offshore wind grouting materials in high chloride ion environment is solved, and the resistance of offshore wind grouting materials has been significantly improved Effects of chloride ion permeability and durability.

CN119462014APending Publication Date: 2025-02-18BEIJING MUHU CONCRETE ADMIXTURE CO LTD

Patent Information

Application Number
CN202411639907.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Offshore wind power grouting materials are susceptible to corrosion and deterioration in high chloride ion environments, resulting in corrosion of steel bars and decreasing material strength, affecting the safety and durability of wind power foundations.

Method used

Using phenols, formaldehyde and amino POSS derivatives as raw materials, a sol-gel reaction occurs through the action of a catalyst to prepare a continuous dense and uniform SiO2/carbon composite aerogel, and add it to the grouting material to improve the Its anti-chlorine ion penetration properties.

Benefits of technology

It significantly improves the anti-chlorine ion permeability of the grouting material, enhances the durability and compressive strength of the material, and ensures the safety and reliability of the offshore wind power foundation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138154320000051
    Figure BDA0005138154320000051
Patent Text Reader

Abstract

The invention provides a chloride ion permeation resistant grouting material and application thereof. The chloride ion permeation resistant grouting material is prepared from the following raw materials in parts by weight: 35 to 40 parts of cement, 45 to 50 parts of quartz sand, 10 to 15 parts of admixture, 0.3 to 0.5 part of expanding agent, 0.1 to 0.3 part of early strength agent, 0.1 to 0.3 part of water reducing agent and 5 to 8 parts of SiO2 / carbon composite aerogel, the SiO2 / carbon composite aerogel is prepared by the following steps: carrying out sol-gel reaction on phenols, formaldehyde and an amino POSS derivative under the action of a catalyst, and drying, carbonizing and grinding the gel. The molar ratio of the phenols to the formaldehyde to the amino POSS derivative to the catalyst is 1: (2.5-4): (0.1-0.3): (0.1-0.3); the composite aerogel has excellent adsorption performance on chloride ions, is used together with a specific expanding agent to inhibit the self-constriction of the grouting material, and has the effects of remarkably improving the chloride ion penetration resistance and compensating the constriction of the grouting material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of grouting materials, and in particular relates to a chloride ion penetration resistant grouting material and application thereof. Background Art

[0002] With the development of offshore wind power construction, the site selection of wind farm construction has gradually moved from the intertidal zone to the sea, with a longer distance from the coast, higher power per unit, greater height, increasing water depth and more complex sea conditions, which puts higher requirements and challenges on the wind turbine foundation connection section. Grouting connection is a typical method for connecting the offshore wind turbine support structure to the pile foundation: the grouting connection is a structural connector composed of two concentric tubular parts, and the annular area between the outer and inner tubes is filled with grouting.

[0003] Cement-based grouting materials are mainly composed of cementitious materials, aggregates, and auxiliary materials. Cement-based cementing materials are mainly cement, and high-performance natural sand or quartz sand can be used as aggregates. Auxiliary materials are various mineral admixtures, admixtures, etc. Cement-based grouting materials are often used for wind power grouting due to their advantages such as good fluidity, high strength, and small shrinkage. They not only play a connecting role in structure and in construction, but also can effectively reduce wind turbine installation errors and fatigue damage. For example, patent CN116693262B discloses a grouting material for offshore wind power conduit frames and its use method, patent CN116514492B discloses a low-temperature, high-fluidity, early-strength wind power grouting material and its preparation method, and patent CN113968698B discloses cement-based grouting material for offshore wind power conduit frames and its application.

[0004] Due to the high concentration of chloride ions in the marine environment, it is easy to cause corrosion and degradation of materials such as concrete. Chloride ions can penetrate into the interior of concrete, destroy its internal structure, and then cause steel corrosion and material strength reduction, seriously affecting the safety and durability of wind power foundations. The above are common offshore wind power cement-based grouting materials, which have high strength and excellent fatigue resistance. They not only have a leveling and supporting effect on the foundation and other structures, but also can reduce stress concentration and fatigue caused by welding, and ensure the normal operation and stability of offshore wind turbines. However, the resistance to chloride ion penetration is general and needs further improvement to ensure the economy and reliability of offshore projects. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a chloride ion penetration resistant grouting material and its application. The raw materials of the grouting material include a sol-gel reaction with phenols, formaldehyde and amino POSS derivatives as raw materials, drying and carbonization to prepare a continuous, dense and uniform SiO2 / carbon composite aerogel. The aerogel has excellent adsorption performance for chloride ions, can significantly improve the chloride ion penetration resistance of the grouting material, and has no adverse effect on the compressive strength of the grouting material.

[0006] In order to achieve the above purpose, the following technical solutions are adopted:

[0007] A chloride ion penetration resistant grouting material comprises the following raw materials in parts by weight: 35-40 parts of cement, 45-50 parts of quartz sand, 10-15 parts of admixture, 0.3-0.5 parts of expansion agent, 0.1-0.3 parts of early strength agent, 0.1-0.3 parts of water reducing agent, and 5-8 parts of SiO2 / carbon composite aerogel; the composite aerogel is prepared by using phenols, formaldehyde, and amino POSS derivatives as reaction raw materials, and undergoing a sol-gel reaction in an organic solvent under the action of a catalyst, and the obtained gel is then dried, carbonized, and ground to obtain the SiO2 / carbon composite aerogel; the molar ratio of the phenols, formaldehyde, amino POSS derivatives, and catalyst is 1:2.5-4:0.1-0.3:0.1-0.3.

[0008] The amino POSS derivative is selected from one or a combination of two of octa-p-aminophenyl-POSS and octaaniline propyl cage-like polysilsesquioxane.

[0009] Amino POSS derivatives are organic / inorganic hybrid materials with a hexahedral structure. Compared with SiO2 aerogels prepared from ordinary siloxane derivatives, the SiO2 aerogels prepared from the amino POSS derivatives have a larger specific surface area, a more stable skeleton, and a more durable and stable adsorption performance for chloride ions. However, the disadvantage is that the formed SiO2 aerogels have poor continuity. The present invention uses phenols, formaldehyde, and amino POSS derivatives as raw materials to react with a catalyst to produce a sol-gel reaction, dry, and carbonize to prepare a continuous, dense, uniform SiO2 / carbon composite aerogel that can be uniformly dispersed in a grouting material system. The aerogel has excellent adsorption performance for chloride ions and significantly improves the anti-chloride ion penetration performance of the grouting material.

[0010] The phenols are selected from one or a combination of two or more of catechol, resorcinol and hydroquinone.

[0011] The catalyst is hexamethylenetetramine.

[0012] The organic solvent is selected from one or a combination of two or more of acetone, butanone, tetrahydrofuran and ethyl acetate.

[0013] Specifically, the SiO2 / carbon composite aerogel is prepared by a method comprising the following steps:

[0014] Phenols, formaldehyde, amino POSS derivatives and catalysts are dissolved in an organic solvent to obtain a mixed solution, and a sol-gel reaction is carried out in a sealed and constant temperature environment. After the reaction, the obtained gel is dried at normal pressure and carbonized and ground in an inert atmosphere to obtain SiO2 / carbon composite aerogel.

[0015] The constant temperature is to control the temperature at 45-80°C, the sol-gel reaction time is 3-5 days, the atmospheric pressure drying is to dry at 60-100°C at atmospheric pressure for 12-48 hours, the carbonization temperature is 700-1000°C and the time is 1-3 hours. The grinding is to grind to an average particle size of 5-10 μm. The molar volume ratio of phenols to organic solvents in the mixed solution is 1 mol: (7-10) L.

[0016] The cement is silicate cement with a strength of 42.5-52.5.

[0017] The quartz sand is continuously graded within a particle size range of 10-120 meshes.

[0018] The admixture is selected from one or a combination of fly ash, silica ash, and mineral powder, preferably a mixture of fly ash, silica ash, and mineral powder in a mass ratio of 8:1-4:1-4.

[0019] The fly ash is selected from one of Class I fly ash, Class II fly ash, and Class III fly ash, or a combination of two or more thereof.

[0020] The SiO2 content of the silica ash is ≥95%, the volcanic ash activity index is ≥95%, and the specific surface area is ≥20000m 2 / kg, loss on ignition ≤5%.

[0021] The specific surface area of ​​the mineral powder is 1400-2000m 2 / kg.

[0022] The expansion agent is selected from one or a combination of two or more of calcium oxide, magnesium oxide, and calcium sulfoaluminate-calcium oxide. The expansion agent can compensate for the shrinkage of the grouting material, prevent cracks caused by shrinkage, and inhibit the invasion of moisture and corrosive ions. The inventors found that SiO2 / carbon composite aerogel has obvious synergistic expansion agent to inhibit the self-shrinkage of the grouting material and compensate for the shrinkage. It is speculated that the porous SiO2 / carbon composite aerogel can improve the toughness of the grouting material and reduce the shrinkage damage caused by internal stress.

[0023] The early strength agent is selected from one or a combination of two or more of chloride early strength agents, sulfate early strength agents, and organic acid salt early strength agents. The early strength agent can accelerate the hydration process, so that the grouting material can reach a higher strength in a short time, which is very important for ensuring the rapid solidification and bearing capacity of the wind power equipment foundation.

[0024] Specifically, the chloride salt early strength agent is selected from one or a combination of two or more of calcium chloride, aluminum chloride, ferric chloride, and potassium chloride; the sulfate early strength agent is selected from one or a combination of two or more of calcium sulfate, sodium sulfate, and potassium sulfate; the organic acid salt early strength agent is selected from one or a combination of two of calcium formate and calcium acetate.

[0025] The water reducing agent has a water reducing rate of 20-25%, and is selected from one or a combination of naphthalene-based water reducing agents and polycarboxylic acid-based water reducing agents. The water reducing agent improves the fluidity and workability of the mixture under the premise of a low water-binder ratio, ensures the high fluidity of the slurry during the construction process, helps to improve the durability and impermeability of the grouting material, and is also conducive to improving construction efficiency and reducing the risk of cracking caused by water evaporation during the construction process.

[0026] The present invention also provides an application of the above-mentioned wind power special grouting material, comprising the following steps:

[0027] The cement, quartz sand, mineral admixture, expansion agent, early strength agent, water reducing agent and SiO2 / carbon composite aerogel are uniformly mixed to obtain grouting material, and then water is added to mix the material, and the mixture is allowed to stand and be exhausted, and then the grouting material can be transported by a grouting machine for pumping construction.

[0028] The mass ratio of the grouting material to water is 1:0.075-0.095.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The raw materials of the grouting material of the present invention include a continuous, dense and uniform SiO2 / carbon composite aerogel prepared by using phenols, formaldehyde and amino POSS derivatives as raw materials through a sol-gel reaction, drying and carbonization with a catalyst. The aerogel has excellent adsorption performance for chloride ions and can be used together with a specific expansion agent to inhibit the self-shrinkage of the grouting material, thereby significantly improving the anti-chloride ion penetration performance of the grouting material and compensating for shrinkage. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0032] Quartz sand was purchased from Fengyang Jihui Quartz Sand Co., Ltd.: 12.5 mesh quartz sand 18wt%, 25.6 mesh quartz sand 27wt%, 48 mesh quartz sand 32wt%, 105.5 mesh quartz sand 23wt%.

[0033] Grade II fly ash was purchased from Hengshui Xiangtong Logistics Co., Ltd.

[0034] Silica ash was purchased from Chengdu Huiye Silica Ash Material Co., Ltd., with SiO2 content ≥ 98%, volcanic ash activity index ≥ 98%, and specific surface area of ​​29000m 2 / kg, loss on ignition 1.5%.

[0035] The mineral powder was purchased from Rizhao Putai Mineral Powder Co., Ltd., with a specific surface area of ​​1640m 2 / kg.

[0036] The polycarboxylic acid-based high-efficiency water-reducing agent was purchased from BASF, with the brand name Melflux1641F and a water-reducing rate of 20%.

[0037] Octa-p-aminophenyl-POSS and octaanilinepropyl caged polysilsesquioxane were purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0038] Calcium sulfoaluminate-calcium oxide expansion agent (HCMA) was purchased from Hangzhou Lidun Concrete Admixture Co., Ltd.

[0039] Example 1

[0040] 1) 1 mol of resorcinol, 4 mol of formaldehyde, 0.3 mol of octa-p-aminophenyl-POSS, and 0.1 mol of hexamethylenetetramine were dissolved in 10 L of butanone to obtain a mixed solution, which was sealed and kept at 80°C for sol-gel reaction for 5 days. After the reaction, the obtained gel was dried at 100°C at normal pressure for 24 hours, carbonized at 900°C in a nitrogen atmosphere for 2 hours, and ground to an average particle size of 9.5 μm to obtain SiO2 / carbon composite aerogel.

[0041] 2) 3.5 kg of silicate cement with a strength of 42.5, 4.5 kg of quartz sand, 1.5 kg of a mixture of Class II fly ash, silica ash, and mineral powder in a mass ratio of 8:3:4, 0.03 kg of calcium sulfoaluminate-calcium oxide expansion agent (HCMA), 0.03 kg of calcium formate, 0.03 kg of water reducer Melflux1641F, and 0.8 kg of SiO2 / carbon composite aerogel are mixed evenly to obtain grouting material, and then water is added according to a mass ratio of grouting material to water of 1:0.090 for mixing, and the mixture is allowed to stand for exhaust, and then the grouting machine can be used for pumping construction.

[0042] Example 2

[0043] The rest is the same as Example 1, except that in step 1), the amount of octa-p-aminophenyl-POSS used is 0.1 mol.

[0044] Example 3

[0045] The rest is the same as Example 1, except that in step 1), an equal molar amount of octaanilinepropyl cage-like polysilsesquioxane is used to replace octa-p-aminophenyl-POSS.

[0046] Example 4

[0047] The rest is the same as Example 1, except that in step 2), the amount of SiO2 / carbon composite aerogel used is 0.5 kg.

[0048] Example 5

[0049] The rest is the same as Example 1, except that in step 2), the amount of calcium sulfoaluminate-calcium oxide expansion agent (HCMA) is 0.05 kg.

[0050] Example 6

[0051] 1) 1 mol of resorcinol, 4 mol of formaldehyde, 0.3 mol of aminophenyl POSS and 0.1 mol of hexamethylenetetramine were dissolved in 10 L of butanone to obtain a mixed solution, which was sealed and kept at 80°C for sol-gel reaction for 5 days. After the reaction, the obtained gel was dried at 100°C at normal pressure for 24 hours, carbonized at 900°C in a nitrogen atmosphere for 2 hours, and ground to an average particle size of 5.2 μm to obtain SiO2 / carbon composite aerogel.

[0052] 2) 4.0 kg of silicate cement with a strength of 42.5, 5.0 kg of quartz sand, 1.0 kg of a mixture of Class II fly ash, silica ash, and mineral powder in a mass ratio of 8:3:4, 0.03 kg of calcium sulfoaluminate-calcium oxide expansion agent (HCMA), 0.03 kg of calcium formate, 0.03 kg of water reducer Melflux1641F, and 0.8 kg of SiO2 / carbon composite aerogel are mixed evenly to obtain grouting material, and then water is added at a mass ratio of 1:0.090 between the grouting material and water for mixing, and the mixture is allowed to stand for exhaust, and then the grouting machine can be used for pumping construction.

[0053] Comparative Example 1

[0054] The rest is the same as Example 1, except that in step 1), an equal amount of aminopropyltrimethylsilane is used to replace octa-p-aminophenyl-POSS.

[0055] Comparative Example 2

[0056] The rest is the same as Example 1, except that in step 1), the amount of octa-p-aminophenyl-POSS is 0.05 mol.

[0057] Comparative Example 3

[0058] The rest is the same as Example 1, except that in step 1), the amount of octa-p-aminophenyl-POSS used is 0.4 mol.

[0059] The wind power special grouting materials prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0060] Vertical expansion rate performance test: Test according to the percentage indicator method in Appendix A of GB / T 50448-2015 Technical Specifications for Application of Cement-based Grouting Materials.

[0061] Chloride ion penetration resistance test: refer to the electric flux method in the standard GB / T 50082-2009 test method for long-term performance and durability of ordinary concrete. The smaller the electric flux of the grouting material, the better its resistance to chloride ion corrosion and the better its durability.

[0062] Compressive strength: Tested in accordance with standard GB / T 17671-2021 cement mortar strength test method, and tested for 28d compressive strength.

[0063] Table 1 Performance test results

[0064]

[0065] It can be seen from the anti-ion penetration performance of Examples 1-2 and Comparative Examples 2-3 that in the process of preparing SiO2 / carbon composite aerogel, as the amount of eight-pairs of aminophenyl-POSS increases within a certain range, the electric flux of the grouting material shows a decreasing trend, indicating that the better its resistance to chloride ion penetration, the better its durability. However, eight-pairs of aminophenyl-POSS exceeds a certain range, and the continuity of SiO2 / carbon composite aerogel is particularly poor and brittle. Too little use will cause SiO2 / carbon composite aerogel to be easily agglomerated and unevenly dispersed in the grouting material system, which will cause the adsorption performance of SiO2 / carbon composite aerogel to chloride ions to deteriorate and the electric flux to increase, that is, the resistance to chloride ion penetration ability deteriorates. The vertical free expansion rate test results also confirm this conclusion. From the results of Comparative Examples 2-3, it can be seen that the dosage of octa-p-aminophenyl-POSS is 0.4 mol, and it is brittle and cannot withstand the gas expansion force generated by the expansion agent in the early stage of hydration of the grouting material. The vertical free expansion rate is relatively large at 0.12%; when the dosage of octa-p-aminophenyl-POSS is 0.05 mol, the SiO2 / carbon composite aerogel has a greater toughness and can not only withstand the internal expansion force of the grouting material in the early stage of hydration, but also resist the shrinkage force of the grouting material in the middle stage of hydration.

[0066] It can be seen from the vertical free expansion rate test results of Example 1, Example 5 and Comparative Example 1 that the SiO2 / carbon composite aerogel has an obvious function of synergizing with the expansion agent to inhibit the self-shrinkage of the grouting material and compensate for the shrinkage.

[0067] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A grouting material resistant to chloride ion penetration, characterized in that: The invention comprises the following raw materials in parts by weight: 35-40 parts of cement, 45-50 parts of quartz sand, 10-15 parts of admixture, 0.3-0.5 parts of expansion agent, 0.1-0.3 parts of early strength agent, 0.1-0.3 parts of water reducing agent and 5-8 parts of SiO2 / carbon composite aerogel; the SiO2 / carbon composite aerogel is a gel obtained by a sol-gel reaction in an organic solvent with phenols, formaldehyde and amino POSS derivatives as reaction raw materials under the action of a catalyst, and the obtained gel is then dried, carbonized and ground to obtain the SiO2 / carbon composite aerogel; the molar ratio of the phenols, formaldehyde, amino POSS derivatives and catalyst is 1:2.5-4:0.1-0.3:0.1-0.

3.

2. The chloride ion penetration resistant grouting material according to claim 1, characterized in that: The amino POSS derivative is selected from one or a combination of octa-p-aminophenyl-POSS and octaaniline propyl caged polysilsesquioxane; the phenol is selected from one or a combination of two or more of catechol, resorcinol and hydroquinone; and the catalyst is hexamethylenetetramine.

3. The chloride ion penetration resistant grouting material according to claim 1, characterized in that: The organic solvent is selected from one or a combination of two or more of acetone, butanone, tetrahydrofuran and ethyl acetate.

4. The chloride ion penetration resistant grouting material according to claim 1, characterized in that: The SiO2 / carbon composite aerogel is prepared by a method comprising the following steps: Phenols, formaldehyde, amino POSS derivatives and catalysts are dissolved in an organic solvent to obtain a mixed solution, and a sol-gel reaction is carried out in a sealed and constant temperature environment. After the reaction, the obtained gel is dried, carbonized in an inert atmosphere and ground to obtain a SiO2 / carbon composite aerogel.

5. The chloride ion penetration resistant grouting material according to claim 4, characterized in that: The molar volume ratio of phenols to organic solvents in the mixed solution is 1 mol:(7-10)L.

6. The chloride ion penetration resistant grouting material according to claim 4, characterized in that: The constant temperature is to control the temperature at 45-80°C, the sol-gel reaction time is 3-5 days, the normal pressure drying is to dry at 60-100°C at normal pressure for 12-48 hours, the carbonization temperature is 700-1000°C and the time is 1-3 hours. The grinding is to grind to an average particle size of 5-10 μm.

7. The chloride ion penetration resistant grouting material according to claim 1, characterized in that: The cement is silicate cement with a strength of 42.5-52.5; the quartz sand is continuously graded within a particle size range of 10-120 meshes; the expansion agent is selected from one or a combination of two or more of calcium oxide, magnesium oxide, and calcium sulfoaluminate-calcium oxide; the early strength agent is selected from one or a combination of two or more of chloride early strength agents, sulfate early strength agents, and organic acid salt early strength agents; the water reducing agent has a water reducing rate of 20-25%, and is selected from one or a combination of two of naphthalene-based water reducing agents and polycarboxylic acid-based water reducing agents.

8. The chloride ion penetration resistant grouting material according to claim 1, characterized in that: The admixture is selected from one or a combination of two or more of fly ash, silica ash, and mineral powder; preferably, it is a mixture of fly ash, silica ash, and mineral powder in a mass ratio of 8:1-4:1-4; the fly ash is selected from one or a combination of two or more of Class I fly ash, Class II fly ash, and Class III fly ash; the silica ash has a SiO2 content of ≥95%, a volcanic ash activity index of ≥95%, and a specific surface area of ​​≥20000m 2 / kg, loss on ignition ≤5%; the specific surface area of ​​the mineral powder is 1400-2000m 2 / kg.

9. Application of the special grouting material for wind power according to any one of claims 1 to 8, characterized in that: The steps include: The cement, quartz sand, mineral admixture, expansion agent, early strength agent, water reducing agent and SiO2 / carbon composite aerogel are uniformly mixed to obtain grouting material, and then water is added to mix the material, and the mixture is allowed to stand and be exhausted, and then the grouting material can be transported by a grouting machine for pumping construction.

10. The use of the chloride ion penetration resistant grouting material according to claim 9, characterized in that: The mass ratio of the grouting material to water is 1:0.075-0.095.

Citation Information

Patent Citations

  • Cement-based grouting material for offshore wind turbine jackets and its application

    CN113968698B

  • A low-temperature, high-fluidity, early-strength wind power grouting material and its preparation method

    CN116514492B

Cited By

  • High-fluidity grouting material and preparation method thereof

    CN120004576A

  • A high-fluidity grouting material and its preparation method

    CN120004576B

  • Impermeable composite admixture, concrete for impervious reinforced concrete drain pipe and preparation method of concrete

    CN122079525A